2023
DOI: 10.1002/fsn3.3253
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and health effects of garlic essential oil: A review

Abstract: Garlic (Allium sativum L.), the underground bulb of the Allium plant in the family Liliaceae, is a common and popular spice that has historically been used to prevent and treat many different diseases such as pain, deafness, diarrhea, tumors, and other healthy problems. Garlic essential oil contains a variety of organosulfur compounds, such as the most representative diallyl disulfides (DADS) and diallyl trisulfides (DATS), which have attracted great interest in medicine, food, and agriculture because of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 128 publications
(136 reference statements)
0
22
0
1
Order By: Relevance
“…The addition of garlic essential oils in chicken ration acted by immunomodulation via bioavailability of nutrients required to synthesize antibodies and promote development of the immune system of chickens ( Elbaz et al, 2022 ). Claims by ( Huang et al, 2023 ) demonstrated that garlic essential oil supports the immune system by improving the phagocytic activity of heterophages and explaining the rate of peroxidation induced by ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of garlic essential oils in chicken ration acted by immunomodulation via bioavailability of nutrients required to synthesize antibodies and promote development of the immune system of chickens ( Elbaz et al, 2022 ). Claims by ( Huang et al, 2023 ) demonstrated that garlic essential oil supports the immune system by improving the phagocytic activity of heterophages and explaining the rate of peroxidation induced by ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] Garlic essential oil (GO) emerges as a novel therapeutic tool with potential benefits in preventing cancer, alleviating oxidative damage and inflammation, preserving liver health, and reducing blood sugar levels. 59 Previous research underscores the promising effects of organosulfur compounds derived from GO, such as diallyl disulfide and diallyl trisulfide, in addressing the multifaceted challenges presented by NAFLD. 60 Lai et al reported that GO and its active compound DAD exhibited anti-NAFLD effects in obese mice by regulating key enzymes and molecules involved in lipid synthesis and metabolism, including SREBP-1c, acetyl-CoA carboxylase, FAS, and PPAR-α.…”
Section: Garlic Essential Oilmentioning
confidence: 99%
“…Inverse vulcanization of diallyl disulfide (DAS), an essential oil of garlic, 145 and myrcene, a natural terpene from thyme, 146 as natural dienes with sulfur at 185 °C produced polysulfides that were suitable candidates for cathodes in Li–S batteries (Fig. 10a).…”
Section: Natural Product Derived Polysulfidesmentioning
confidence: 99%